Females with a disability and participation in sport / Tracy Taylor, Simon Darcy and Dan Lock - Taylor, Tracy; Darcy, Simon; Lock, Dan (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2012)
It is well proven that a physically active lifestyle has associated health and social benefits and is linked to a sense of wellbeing. It is also acknowledged that not all groups in society have the same opportunities to engage in sport and physical activity, and that participation can be gendered. This paper presents a study of the sport participation of females with a disability within Australia to better understand some of the key drivers to enhance levels of involvement in sport and thus facilitate a healthier lifestyle. The research design employed an online questionnaire available for completion in nine formats depending on the disability type and the support needs of individuals responding. Questions sought both quantitative responses about levels of participation and qualitative responses about the constraints experienced and benefits received from participation. Some 266 women with disability responded, of which 86% indicated that they were active sport and recreation participants. The results show higher levels of participation by women who were independent or had lower to moderate support needs compared with women with high to very high support needs who had substantially lower levels of participation. Yet, when examining the constraints that these groups faced, rather than being intrapersonal in nature (e.g. the individual's impairment) there were a series of interpersonal (e.g. no one to participate with) and structural (e.g. government support) issues that constrain participation. The constraints were then examined from the perspective of those outside of sporting context those within the sporting context. For those who did participate, the benefits were identified as a sense of achievement together with improving health. The other key benefits were overwhelmingly social in nature, including belonging, companionship and having time with friends. The implications for sport and active recreation involvement generally and for sport participation in particular are discussed.